STRATEGI KELAS MENENGAH DALAM MENGHADAPI MIDDLE-INCOME TRAP: ANALISIS KONTEN YOUTUBE - Adam Hafidz Al Fajar; Sriharini (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2024)
The middle-income trap (MIT) represents a significant challenge for emerging economies like Indonesia, where middle-class stagnation obstructs the transition to high-income status. This study explores strategies for the middle class to overcome MIT by analyzing YouTube content from channels such as Timothy Ronald and Satu Persen. Using a qualitative approach with content analysis methods, the research identifies recurring themes in economic challenges and proposed solutions. Data collection involved thematic analysis of relevant videos discussing productivity enhancement, education, and innovation strategies. The findings indicate that overcoming MIT requires a shift from consumption-driven to innovation-led economic contributions, emphasizing skill development, financial planning, and adaptation to technological shifts. The study highlights the potential of digital platforms as tools for public education and empowerment, aiming to equip the middle class with actionable strategies to drive sustainable economic transformation..